THE EFFECT OF EMPLOYEE EMPOWERMENT AND INTRINSIC MOTIVATION ON ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE - Andika, Rudi; Darmanto, Susetyo (Jurnal Aplikasi Manajemen, 2020)
The main task of the government is to provide the best service to its citizens. The purpose of this study is to analyze the influence of empowerment and intrinsic motivation toward employee performance with a mediating role of organizational commitment. The research sample consisted of 104 employees at the Civil Registry Office of the Semarang City Government. The data carried out in 2018 and processed with a Partial Least Square Structural Equation Modeling (PLS SEM) using SmartPLS 3.2.8 Profesional License. The result of the analysis shows that empowerment and intrinsic motivation have significant effects on organizational commitment. The research results also find the significant effect of empowerment, intrinsic motivation, and organizational commitment on employee performance. The next research can be done by testing aspects of the organization, both those that are interpersonal within departments and relationships between departments